Water Quality Near Phosphatic Fertilizers Plant at Paradeep - Jena, S.; Bhattamisra, S.D. (Asian Journal of Chemistry, 2010)
Pardeep, located beside NH-5, is a port town in India with large industrial activity. Two phosphate based fertilizer plants are located here. Effluent water from the plants are fed to a creek to be released eventually to river Mahanadi. The water from the creek is slightly turbid, having slow sedimentation causing greyish precipitate. The water sample were characterized in terms of pH, density, total hardness and concentration of metal ions like iron, aluminium, sodium, potassium, magnesium and calcium. Presence of fluoride, phosphate, sulphate and chloride in the water sample has also been ascertained. Some measures for effluent treatment have been suggested to check water pollution.